(3QO eG EfJbO Ydi GdTGaYi QVi Gddg Yfgs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO abO EfJbO HYV GdeNGdajf Ydi GdEeGe CHj YHO Gddg eMeO GHf EOQjS GdTGaYi MQhakG ef GdYQHjI RYehG Cfg NGda ajgG GdYQHjI s
(3BNQgG (B:s
(3hef Pdc Cf bGdhG bGd GdTGaYi hJJQc GdYQH hGdNfGaS adG JCcdgG hbGd GdNRQfLi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdejcQhajde eUhQ eQJjf fSNJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B837s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdabg GdESdGejs